SWOT Analysis of PT XYZ by Identifying Strengths and Challenges in the Company - Dhea Anggraeni; Hapzi Ali (Siber International Journal of Sport Education, 2024)
This tudy focuses on disecting the strategic positionig of PT.XYZ by employing the SWOT analysi framework. Through this research, the internal elments of the company are identified, namely advantages (Strengths) and limitations (Weakneses), as wel as external aspects consiting of oportunities (Oportunities) and risks (Threats). The primary objective of this analysi is to formulate a suitable strategy for PT. XYZ in maintainig its competiivenes and confronting various obstacles within its busines landscape. The method aplied is descriptive qualitative, with information gathered through literature review, direct observation, and conversations with relvant parties at PT. XYZ. The findings from the SWOT analysi are xpected to provide a comprehensive understanding of the company's trategic standing and serve as a foundation for future strategic decision making.